Modern Strategies for Controlling Wind Power Plants: Technologies, Challenges and Prospects - Nazarii Kurylko; Roman Fedoryshyn (Energy Engineering and Control Systems, 2024)
This paper explores the evolution of wind power plant (WPP) control strategies, from simple approaches aimed at optimizing the operation of individual wind turbines to the development of more complex systems that manage WPPs as single integrated entities. Particular attention is paid to the key requirements for WPP control systems and the analysis of WPP structure, especially in the context of their integration into the overall power system. The main objectives of WPP control systems have been studied. The paper presents a detailed review and analysis of the control strategies that are being actively investigated. The control strategies that have successfully found commercial application are identified, and directions for further research needed to optimize and improve these strategies are outlined.